TINJAUAN HUKUM ATAS PEMBELIAN TERSELUBUNG (UNDERCOVER BUY) DALAM MENGUNGKAPKAN TINDAK PIDANA NARKOTIKA OLEH KEPOLISIAN REPUBLIK INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Rizky Fahrezi, Fahmi; Lumban Gaol, Selamat (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
In disclosing narcotics crimes, the police can act according to their own judgment as long as it is within their authority. The disguised purchasing technique is one of the police's ways of uncovering narcotics crimes. Therefore, it is very interesting and important to study further about how undercover buying techniques are regulated in uncovering narcotics crimes by the National Police of the Republic of Indonesia based on Law Number 35 of 2009 concerning Narcotics? and how are undercover buy techniques implemented in uncovering narcotics crimes by the National Police of the Republic of Indonesia? To answer these problems, normative juridical legal research methods are used with statutory and conceptual regulatory approaches. Data obtained from primary, secondary and tertiary legal material sources were collected and then analyzed using qualitative data analysis techniques. From the research results it was found that Article 79 of the Narcotics Law no. 35 of 2009. Protection for the implementation of covert purchasing techniques is also basically protected by the Criminal Procedure Code and the Police Law. undercover purchase method (Undercover Buy) by investigators, namely the role of covert purchase techniques in disclosing narcotics crimes is in the process of investigating narcotics crimes which is justified by law, namely Law no. 35 of 2009 concerning Narcotics.